Three-year trends in literature on artificial intelligence in ophthalmology and vision sciences: a protocol for bibliometric analysis - Tina Felfeli; Laura Banfield; Hayley Monson; Jeff Demaine (BMJ Health & Care Informatics, 2022)
Introduction The aim of this study is to provide an insight into the literature at the intersection of artificial intelligence and ophthalmology.Methods and analysis The project will be performed in four key stages: formulation of search terms, literature collection, literature screening and literature analysis. A comprehensive search of databases including Scopus, Web of Science, Dimensions and Cochrane will be conducted. The Distiller SR software will be used for manual screening all relevant articles. The selected articles will be analysed via R Bibliometrix, a program for mathematical analysis of large sets of literature, and VOSviewer, which creates visual representations of connections between articles.Ethics and dissemination This study did not require research ethics approval given the use of publicly available data and lack of human subjects. The results will be presented at scientific meetings and published in peer-reviewed journals.